Umami Ingredient, a newly developed flavor enhancer from shiitake byproducts, in low-sodium products: A study case of application in corn extruded snacks - Harada-Padermo, Samara dos Santos (2021)
Although it is not an easy task, sodium reduction in food is necessary, and in this scenario, the research for tasty food with reduced sodium content has an extremely relevant role. In this study, sodium reduction in corn extruded snacks was evaluated. Four snack samples were evaluated: one control sample (with salt and monosodium glutamate) and three reduced-sodium formulations. To minimize sensory losses caused by sodium reduction, monosodium glutamate (MSG) and Umami Ingredient (a new flavor enhancer ingredient obtained from shiitake mushroom byproducts) were used as flavor enhancers, since the utilization of Umami Ingredient enables the development of MSG-free and low-sodium products. The physical (expansion ratio, density and cutting force) and sensory (acceptance through hedonic scale, Just-about-right scale and characterization by the Rate-All-That-Apply method) characteristics of the snacks were investigated. Snacks with lower sodium content exhibited lower acceptance compared to the control sample, but they were not rejected by the consumers. Umami Ingredient performed similarly to MSG on seasoning flavor, salty and umami tastes. From this result, Umami Ingredient can be considered a potential alternative to replace MSG in low-sodium food, acting as a flavor enhancer and contributing to reducing the use of additives in the product formulation.